Provisioning the requirement: machine gun needs of the British expeditionary force in France, 1914-1916 - Fisher, Richard (Helios House Press, 2023)
At the outbreak of the First World War, the British Army was in the process of replacing its Maxim machine guns with the Vickers machine gun it had adopted in 1912. Although both weapons were of the same calibre and shared some common accessories, they were not wholly compatible. Furthermore, with the expansion of the British Expeditionary Force and the concomitant need to increase its automatic firepower, the introduction of more machine guns had to be managed with increased demand and complexity, with additional new models introduced as the war progressed. By analysing the war diaries of the lines of communication, this article evaluates the rollout of the Vickers and later models, and the implications their introduction had on logistics, personnel, and organisation across the Force. It is hoped this approach will offer an insight into the prioritisation and decision-making of this critical period, as well as an opportunity to understand the growing importance of the machine gun ahead of the formation of the Machine Gun Corps in October 1915.
Keywords: Great Britain; Maxim; Lewis; Vickers; machine guns; First World War; Machine Gun Corps